THE COMMUNITY SERVICE TO CREATE PACKAGING DESIGN FOR BATIK SILABANGO - Miftahul Choiron; Bertung Suryadharma; Ardiyan Dwi Masahid; Winda Amilia; Andrew Setiawan Rusdianto (UNEJ e-Proceeding, 2022)
Batik is an ancestral art which is Indonesia's cultural wealth. Each region has a distinctive motif that characterizes the origin of the batik. Silabango Batik is batik developed by one of the MSMEs in Arjasa village, Arjasa sub-district, Jember district. The uniqueness, beauty, and exclusivity of Silabango's hand-written batik motifs have not been packaged properly, so they are not in accordance with the branding they want to create. Therefore, this community empowerment aims to build the brand image of Silabango batik through the development of packaging designs. Packaging is designed using white paper, 200 grams grammatical, single wall for exclusive product packaging, packaging for premium products using kraft paper, 140 gram grammatical, single wall. Keywords: batik, packaging,color, SME